Mutations in ARX result in several defects involving GABAergic neurons - Friocourt, Gaelle; Parnavelas, John G. (Frontiers in Cellular Neuroscience, 2010)
Genetic investigations of X-linked mental retardation have demonstrated the implication of ARX in a wide spectrum of disorders extending from phenotypes with severe neuronal migration defects, such as lissencephaly, to mild or moderate forms of mental retardation without apparent brain abnormalities, but with associated features of dystonia and epilepsy. These investigations have in recent years directed attention to the role of this gene in brain development. Analysis of its spatio-temporal localisation profile revealed expression in telencephalic structures at all stages of development, mainly restricted to populations of GABA-containing neurons. Furthermore, studies of the effects of ARX loss of function either in humans or in lines of mutant mice revealed varying defects, suggesting multiple roles of this gene during development. In particular, Arx has been shown to contribute to almost all fundamental processes of brain development: patterning, neuronal proliferation and migration, cell maturation and differentiation, as well as axonal outgrowth and connectivity. In this review, we will present and discuss recent findings concerning the role of ARX in brain development and how this information will be useful to better understand the pathophysiological mechanisms of mental retardation and epilepsy associated with ARX mutations.